Evaluation of Incompatibility Group I1 (IncI1) Plasmid-Containing Salmonella enterica and Assessment of the Plasmids in Bacteriocin Production and Biofilm Development - Kaldhone, Pravin R.; Carlton, Ashlyn; Aljahdali, Nesreen; Khajanchi, Bijay K.; Sanad, Yasser M.; Han, Jing; Deck, Joanna; Ricke, Steven C.; Foley, Steven L. (Frontiers in Veterinary Science, 2019)
Mobile genetic elements, such as plasmids, can potentially increase the ability of bacteria to infect and persist in vertebrate host cells. IncI1 plasmids are widely distributed in Salmonella from food animal sources and associated with clinically important strains. These plasmids often encode antimicrobial resistance; however, little is known about their impact on the virulence of Salmonella strains. To assess the potential impact of the plasmids on virulence, 43 IncI1-positive Salmonella isolates from human and animal sources were subjected to whole genome sequence (WGS) analyses and evaluated for their abilities to invade and persist for 48 hours in Caco-2 human intestinal epithelial cells, form biofilms and encode bacteriocins. Draft WGS data were submitted to predict the presence of virulence and antimicrobial resistance genes, plasmid replicon types present, conduct plasmid multilocus sequence typing (pMLST), and core genome MLST (cgMLST) in the isolates. Caco-2 cells were infected with Salmonella strains and incubated for both one and 48 hours for the invasion and persistence assays, respectively. Additionally, Salmonella isolates and IncI1 plasmid carrying transconjugants (n=12) generated in Escherichia coli were assessed for their ability to produce biofilms and bacteriocin inhibition of growth of other bacteria. All Salmonella isolates infected Caco-2 cells and persisted in the cells at 48 hrs. Persistent cell counts were observed to be significantly higher than invasion assay cell counts in 26% of the isolates. Among the IncI1 plasmids, there were 18 pMLST types. Nearly 35% (n=15) of Salmonella isolates produced biofilms; however, none of the IncI1-positive transconjugants produced increased biofilms compared to the recipient. Approximately 65% (n=28) of isolates and 67% (n=8) of IncI1-positive transconjugants were able to inhibit growth of at least one E. coli strain; however, none inhibited the growth of strains from species other than E. coli. The study characterized IncI1 positive Salmonella isolates and provided evidence about the potential contributions of IncI1 plasmids virulence phenotypes and areas where they do not. These findings should allow for more focused efforts to assess the impact of plasmids on bacterial pathophysiology and human health.